'We Have to Pay the Price': German Workers and the US Army, 1945–1989. (November 2019) - Seipp, Adam R.
This article examines the relationship between German civilian workers and the United States Army in the Federal Republic of Germany during the Cold War. Using archival and published sources, the article offers an entangled history of 'local national' employees and their role in maintaining the American presence in Central Europe. Beginning in the late 1960s, German labour unions began to challenge American labour policy. In doing so, they consistently argued for a more forceful assertion of German sovereignty. This labour relationship was therefore important for both the military history of the Cold War and for the development of German democracy.